Advanced power cycles for coal-fired power plants based on calcium looping combustion: a techno-economic feasibility assessment - Michalski, Sebastian; Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2020)
Carbon capture and storage is crucial to decarbonising the power sector, as no other technology can significantly reduce emissions from fossil fuel power generation systems. Yet, the mature CO2 capture technologies result in net efficiency penalties of at least 7% points. Emerging technologies, such as calcium looping combustion, can reduce the net efficiency penalty to 2.4% points. Further reductions can be achieved by replacing the conventional steam cycle with advanced power cycles. This study aimed to assess the techno-economic feasibility of the coal-fired power plant based on calcium looping combustion with different advanced Brayton cycles. These included single power cycles, such as recompression supercritical CO2, simple supercritical CO2 cycle, and xenon cycle, as well as combined power cycles based on helium, nitrogen and recompression supercritical CO2 cycles. The net efficiency and break-even electricity price, which was estimated using the net present value method, were used as the key techno-economic performance indicators. A parametric study was also conducted to assess the impact of the key thermodynamic parameters. This study showed that the case based on a single recompression supercritical CO2 cycle had the best overall techno-economic performance, while the recompression supercritical CO2 combined cycle case had the best techno-economic performance among combined cycle cases. The former was characterised with a net efficiency of 38.9%, which is higher than that of the reference coal-fired power plant without CO2 capture (38.0%). Such performance was achieved at a break-even electricity price of 71.2 €/MWel,neth, corresponding to a cost of CO2 avoided of 16.3 €/tCO2.
Keywords: efficiency penalty; carbon capture; clean power technologies; clean coal; carbonate looping; advanced power generation